Stillwater [videorecording (DVD)] - McCarthy, Tom, 1966-; Damon, Matt; Cottin, Camille; Breslin, Abigail, 1996-; Siauvaud, Lilou; Dunagan, Deanna (Focus Features : Universal, 2021)
A father travels from Oklahoma to France to help his estranged daughter, who is in prison for a murder she claims she didn't commit.